A New 3-D Chaotic System with Conch-Shaped Equilibrium Curve and its Circuit Implementation - Mamat, Mustafa; Vaidyanathan, Sundarapandian; Sambas, Aceng; Afendee, Mohamad; Sampath, Sivaperumal; Sanjaya, Mada (International Journal of Engineering and Technology, 2018)
This paper reports the finding a new chaotic system with a conch-shaped equilibrium curve. The proposed system is a new addition to existing chaotic systems with closed curves of equilibrium points in the literature. Lyapunov exponents of the new chaotic system are studiedfor verifying chaos properties and phase portraits of the new system via MATLAB are unveiled. An electronic circuit simulation of the new chaotic system with conch-shaped equilibrium curve is shown using MultiSIM to check the model feasibility.